Comparative evaluation of fracture resistance of teeth obturated using three different systems - AH plus/Gutta-percha, Resilon/Realseal self-etch, and Endofill/Gutta-percha: An in vitro study - G Ratna Velugu; P Karunakar; M S Ranga Reddy (Wolters Kluwer Medknow Publications, 2016)
Introduction: Endodontically treated teeth are more prone to fracture under masticatory forces. Resin-based dental materials have been proposed as a means to reinforce an endodontically treated tooth through the use of adhesive sealers in the root canal system. Aims: The objective of this study is to evaluate the fracture resistance of endodontically treated teeth obturated using lateral compaction technique with AH plus/Gutta-percha, Resilon/RealSeal self-etch (SE), and Endofill/Gutta-percha. Subjects and Methods: In this study, sixty, single-rooted mandibular premolars were used. The teeth chosen were de-coronated with a diamond disc and the root length was 14 mm for each specimen. All teeth were enlarged up to ISO size 30 master apical file using Ni-Ti rotary Protaper system and crown-down technique. Instrumented teeth were then randomly assigned into four experimental groups (n = 15) as follows: Group 1 - obturated with AH plus/Gutta-percha, Group 2 - obturated with Resilon/RealSeal SE, Group 3 - obturated with Endofill/Gutta-percha, and Group 4 - no obturation was done (control). The specimens were embedded into auto-polymerizing resin, later mounted in the universal testing machine and were subjected to load at a crosshead speed of 1.0 mm/min until the root fractured. Statistical Analysis Used: ANOVA and Duncan post hoc analysis. Results: Results of this in vitro study showed that Resilon/RealSeal SE showed better fracture resistance of all the materials tested. Statistically significant difference between the groups (<0.001) was observed. Conclusions: Resilon/RealSeal SE demonstrated higher fracture resistance values than AH plus/Gutta-percha, followed by Endofill/Gutta-percha